EFEKTIFITAS METODE LATIHAN MELALUI TEKNIK MENEMPEL UNTUK MENINGKATKAN KETERAMPILAN MENDESAIN JILBAB DARI KAIN BORKAT PADA ANAK TUNAGRAHITA RINGAN - Lasri Dewita (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstrack: This research was conducted based on the problem found in the field indicated that a student with mild mental retardation in the third grade of SMALB C at SLB Negeri 1 Padang was not yet able to design veils made of brocade. This problem was assumed arose as training method had not been applied yet at school. This was an experimental research which was conducted in the form of Single Subject Research (SSR) by using A-B-A design. The data collected was analyzed by using visual analysis of graphic. The subject of the research was a student with mild mental retardation. The assessment was done by measuring the percentage of the student’s ability in the scale of attitude and action to design beils made of brocade. Kata-kata kunci: Latihan; Mendesain jilbab; Kain Borkat; Tunagrahita Ringan